Sindbis Virus Antibody Seroprevalence in Central Plateau Populations, South Africa - Kennedy, Nicole; Goedhals, Dominique; Vawda, Sabeehah; Bester, Philip Armand; Burt, Felicity (Emerging infectious diseases, 2022)
We report a higher percentage of Sindbis virus-specific IgG in serum from patients attending a rheumatology clinic (18.8%) compared with healthy residents (9.6%) and patients with acute febrile illness (9.4%) in Free State Province, South Africa. Sindbis virus infection should be considered a potential cause of arthritis in South Africa.